Analysis of lower limb alignment in overweight children. - Alessandra Rezende Martinelli; Moisés Oliveira Purga; Alessandra Madia Mantovani; Marcela Regina Camargo; Alan Abrão Rosell; Cristina Elena Prado Teles Fregonesi; Ismael Forte Freitas Junior (Universidade Federal de Santa Catarina, 2011)
Overweight and obesity have reached epidemic proportions, especially among schoolchildren, and have become a global health problem. Many adaptations in postural organization are observed in overweight and obese children, which have serious consequences. Posture assessment contributes to the understanding of these changes. The aim of this study was to assess changes in lower limb posture of overweight and obese children using a specific method. Twenty-two subjects, 9 girls and 13 boys, aged 5-9 years participated in the study. Posture was assessed by photogrammetry using the SAPo software. The lower limb joint angles and plantar projection of the center of gravity were analyzed. Nonparametric and descriptive statistics were used, in addition to the Kruskal-Wallis and Mann-Whitney tests (p < 0.05) for comparison between genders. Both groups showed anterior pelvic tilt and slight rotation (to the right in girls and to the left in boys), hyperextension, and valgus knees and ankles. The center of gravity presented 26.95% anteriorization. In conclusion, posture assessment in this population was consistent with literature findings and the method used permitted the quantification of data for future comparisons.